Solid-liquid stable phase equilibria of the quaternary system Na+ //Cl−, SO42−, CO32−-H2O and its subsystems Na+ //Cl−, CO32−-H2O and Na+ //SO42−, CO32−-H2O at 353.15 K. (April 2020) - Ge, Shao-Ying; Zhu, Li; Ma, Yu-Long; Liu, Er; Zhao, Kang-he
Highlights: Phase diagrams for the system Na + //Cl −, SO4 2−, CO3 2− -H2 O at 353.15 K. Phase diagrams for the subsystems Na + //Cl −, CO3 2− -H2 O and Na + //SO4 2− CO3 2− -H2 O at 353.15 K. Completed determination of monohydrate and anhydrous double salt using XRD analysis. Abstract: The solid-liquid phase equilibria of the solution in the quaternary system Na + //Cl −, SO4 2−, CO3 2− -H2 O and its subsystems Na + //Cl −, CO3 2− -H2 O and Na + //SO4 2−, CO3 2− -H2 O at 353.15 K were measured by isothermal solution saturation method. The equilibrium solids were determined by the Schreinemaker's method of wet residues and X-ray diffraction (XRD). Based on the experimental data, the phase diagrams were plotted and analysed. There is one monohydrate in the ternary system Na + //CO3 2−, Cl − -H2 O at T  = 353.15 K, and the phase diagram contains one invariant point, two univariant curves and four crystallization regions. The ternary system Na + //SO4 2−, CO3 2− −H2 O at T  = 353.15 K is more complex than the previous system since one monohydrate and one anhydrous double salt are found; the phase diagram contains two invariant points, three univariant curves and six crystallization regions. The phase diagram of the quaternary system Na + //Cl −, SO4 2−, CO3 2− -H2 O at 353.15 K includes two invariant points, five univariant curves, and four crystallization fields of single salts corresponding to NaCl, Na2 SO4, Na2 CO2 ·H2 O and 2Na2 SO4 ·Na2 CO2 . The results obtained in this study can help identify the solutions from which fractional crystallization of Na2 SO4 and NaCl will be more effective.